Using an Effective Numerical Method for Solving a Class of Lane-Emden Equations - Yulan Wang; Hao Yu; Fugui Tan; Shuguang Li (Abstract and Applied Analysis)
We use the reproducing kernel method to solve the well-known classes of Lane-Emden-type equations. These classes of equations have the form of Lane-Emden problem. Comparing the results of the reproducing kernel method with the analytical solutions by means of some typical examples, we can affirm that the reproducing kernel method is an efficient and accurate method.